Rectal hyperplasia after jejunoileal bypass for morbid obesity. Issue 11 (November 1988) - Appleton, G V; Wheeler, E E; Al-Mufti, R; Challacombe, D N; Williamson, R C
Abstract : Jejunoileal bypass (JIB) has been widely used to treat patients with morbid obesity for the past 20 years. In rats JIB causes adaptive colonic hyperplasia and enhances colorectal neoplasia. In this study crypt cell production rate (CCPR) was measured stathmokinetically in cultured rectal biopsies from nine patients with JIB and seven controls without intestinal operations or disease. Crypt cell production rate in the group with JIB was more than double that of controls (12.80 (2.67) v 6.23 (1.49) cells/crypt/h: p less than 0.001). There were no significant differences in crypt morphometry and histological examination of rectal biopsies was normal. Patients with JIB have a marked and persistent increase in cell proliferation in the large intestine and may be at increased risk of developing colonic cancer.